Reflections on Positive Emotions and Upward Spirals - Fredrickson, Barbara L. (Perspect Psychol Sci, 2018)
We reflect on Fredrickson and Joiner ((2002) Positive emotions trigger upward spirals toward emotional well-being. Psychological Science, 13, 172–175.) and the impact this research report has had both within and beyond psychological science. This article was both one of the first publications to provide empirical support for hypotheses based on the broaden-and-build theory of positive emotions and a product of the genesis of positive psychology. We highlight empirical and theoretical advancements in the scientific understanding of upward spiral dynamics associated with positive emotions, with particular focus on the new upward spiral theory of lifestyle change. We conclude by encouraging deeper and more rigorous tests of the prospective and reciprocal relations associated with positive emotions. Such progress is needed to better inform translations and applications to improve people’s health and well-being.